Pengembangan E-module Berbasis Discovery Learning Berbantuan PhET Pada Materi Teori Kinetik Gas Untuk Mahasiswa - Shinta Dewi Susanti; Muhammad Reyza Arief Taqwa; Sulur Sulur (Jurnal Pendidikan Fisika dan Teknologi (JPFT), 2020)
This research was conducted to develop discovery learning-based E-modulees combined with PhET in kinetik gas theory materials with the aim of: 1) producing discovery learning-based E-modulee products in the analysekinetik theory of gassesmaterial subjects for students. (2) knowing the feasibility of discovery learning-based E-modulee products in kinetik gas theory material for students. referring to the R&D (reaserch and development) method of the step of development refers to Thiagarajan (4D) which has been adapted to the purpose of research only until the development stage. The development procedures in this study include define, design, and development. This research resulted in a product in the form of discovery learning based emodules on the subject matter of kinetik gas for students with a decent category. Based on the results of validation by experts, the overall product feasibility percentage is 87.7%, which means that the product falls into very valid criteria. The readability test conducted on 14 students of physics education UM obtained an average reading result of 96.4% of the readability criteria included in the legible category.